STRATEGI PEMBERDAYAAN MASYARAKAT BERBASIS KONTEKSTUAL DI PKBM AL MADINAH KOTA KEDIRI - rochman, abdur; Supriyono, Supriyono; Supriyanto, Achmad; Zulkarnain, Zulkarnain; Sri Redjeki, Endang (ABIDUMASY Jurnal Pengabdian Kepada Masyarakat, 2024)
Society is a human being who plays a role in increasing the capacity of life so that it continues to survive as it should. As an effort to increase capacity, educational institutions are needed that are not only formal in nature, but can also be done through non-formal education as a form of effort to develop society equally. Non-formal educational institutions that support equal communities include the Community Learning Activity Center (PKBM) which was formed by the community for the community which has an initiative movement to educate society in general through non-formal education. PKBM has an important role in empowering communities contextually to improve competitive and competitive community skills. The research method used is a qualitative approach with a case study research design. The research was carried out at PKBM Al Madinah, Kediri City, where non-formal education is carried out with very comprehensive coverage, including special packages for pursuing packages A, B and C, and other relevant learning programs. There are several unique findings found in PKBM Al Madinah in supporting contextual community empowerment. So the role of PKBM Al Madinah Kediri City is considered very important in providing learning space for the community in supporting abilities.